Es muss zusammenkommen, was zusammengehört: Caritasarbeit im real existierenden Sozialismus in der ehemaligen DDR - Puschmann, Hellmut (European Journal of Mental Health, 2008)
Parts that Belong Together are to Join: Charitable Work in the Real Socialism of the Former GDR: In the former GDR the Catholic Church was able to establish comprehensive charitable activities that to a large extent were based on the resources of the faithful, and therefore had close ties with parish communities. Help could be extended not only at the level of church communities, but also through numerous institutions like homes for the elderly, hospitals, and homes and resorts caring for people with mental disabilities. These were also gladly visited by people who did not belong to the church. The church was allowed to carry out this work independently, without direct state control. Financial and professional support from the German Catholic Bishops’ Conference, the German Caritas Association, the Bonifatiuswerk organisation of German Catholics and certain private individuals were decisive in enabling these activities. When following the reunification of Germany the charitable organisation responsible for the individual East German public administration regions could again become an official member of the German Caritas Association; progress along a common path that was hindered but never prevented by politics could continue.